Spanish designer fashion brand analysis - Barbero, Giulia; Sarget Tarifa, Marisa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Despite the repercussions of the pandemic, many fashion companies have invested efforts in meeting key challenges for their survival, including internationalization and digitization. However, the designer fashion industry stands out, and within an environment dominated by sustainability, has become the answer to uncertainties and social needs due to its distinctive features. The key to amplifying its valuable contribution to the current social, economic and environmental scenario lies in the implementation of solid and relevant branding strategies.